THEORETICAL RESEARCH OF THE DRYING PROCESS OF WALNUTS USING VIBRATION TECHNOLOGIES - TSURKAN, OLEH; RUTKEVYCH, VOLODYMYR; DIDYK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The question of increasing the quality indicators of walnuts in the process of storage and processing is considered, due to theoretical studies of the process of drying walnuts in a vibrating machine.Based on the analysis of scientific research on this topic, it was established that the use of vibration technologies increases the efficiency of drying walnuts and allows to reduce the drying time by 30-40 % compared to traditional methods. In addition, vibration technologies allow to preserve the quality of nuts, reducing the effect of heat on their structure.It is noted that vibration technologies improve the drying process by stimulating the movement of moisture from the surface of walnuts. At the same time, various types of vibration are used in practice, such as linear, oscillatory, centrifugal and ultrasonic.A structural and technological diagram of a vibrating machine for drying walnuts in the shell has been developed. During vibration drying in a vibrating machine, a walnut is placed on a vibrating surface that generates mechanical vibrations that help distribute heat and moisture throughout the walnut. The use of the proposed design of the vibrating machine for drying volos mountains allows to achieve a more uniform and rapid removal of moisture from the product.As a result of theoretical studies, it was established that vibration drying is an effective method for drying walnuts, which allows you to preserve product quality and reduce energy costs. To achieve the set results, it is necessary to observe optimal drying parameters, such as temperature, relative humidity and amplitude of vibration movement.It is also stated that the use of vibration technologies in the process of drying walnuts is a promising direction of research that can improve the economic efficiency and quality of walnuts.
Keywords: walnut; drying equipment; vibration; vibration machine; productivity; energy efficiency; costs; humidity